2017
DOI: 10.5961/jhes.2017.242
|View full text |Cite
|
Sign up to set email alerts
|

Preservice teachers’ career adaptability towards teaching profession

Abstract: Bu araştırmanın amacı "pedagojik formasyon eğitimi" kurslarına katılan öğretmen adaylarının kariyer uyumlarını demografik değişkenlere göre incelemektir. Ayrıca araştırmanın diğer bir amacı kariyer uyum puanı yüksek ve düşük olan öğretmen adaylarının kariyer uyumlarına yönelik görüşlerini incelemektir. Araştırmanın modeli karma yönteme dayanmaktadır. Bu kapsamda araştırmanın ilk aşamasında 192 kadın, 68 erkek olmak üzere toplam 260 öğretmen adayına ulaşılmıştır. Nicel verilerin toplanmasında 'Kariyer Uyumu ve … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 7 publications
(14 reference statements)
2
9
0
1
Order By: Relevance
“…From the findings can be seen that it is the career of graduates most substantial being in the area of business education, started to become educators, officials, entrepreneurs, and researchers. This study complement what Erus et al find on their study [6] and Teder [20] relate to multiple jobs, that pre-service teacher education can lead to various field of careers. Nevertheless, in this study, the choice taking of teaching as a profession related to their pre-preliminary teacher competences as an earlier study.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…From the findings can be seen that it is the career of graduates most substantial being in the area of business education, started to become educators, officials, entrepreneurs, and researchers. This study complement what Erus et al find on their study [6] and Teder [20] relate to multiple jobs, that pre-service teacher education can lead to various field of careers. Nevertheless, in this study, the choice taking of teaching as a profession related to their pre-preliminary teacher competences as an earlier study.…”
Section: Discussionsupporting
confidence: 86%
“…As far as this experience obtains, the education and training of professionals impacted positively on the performance of teachers [4] [5] and their career adaptability. [6].…”
Section: Introductionmentioning
confidence: 99%
“…In the study, it was found that gender is not a significant variable when it is investigated whether gender causes a difference on career adaptability. Similarly, Erus & Zeren (2017) were found no significant difference between pedagogical formation students' career adaptability by gender. Career adaptability is closely related to variables such as resilience, optimism, future perspective, adaptation, hope and proactive personality, which are the basic concepts of positive psychology (Büyükgöze-Kavas, 2016;Fasbender et al, 2019;Karacan-Özdemir & Yerin-Güneri, 2017;Rudolph, Lavigne & Zacher).…”
Section: Resultsmentioning
confidence: 75%
“…One of the findings of the study is that students' career adaptability levels did not show any statistically significant difference according to gender. In the literature, there are studies supporting (Erus & Zeren, 2017;Ghosh & Fouad, 2017) and not supporting (Coetzee & Harry, 2015;Han & Rojewski, 2015;Eryılmaz & Kara, 2018;Kahya & Ceylan, 2018) this finding. The developmental guidance approach emphasizes that occupations are not classified according to gender and that there are no gender differences for occupations.…”
Section: Discussion Conclusion and Recommendationsmentioning
confidence: 93%
“…In addition, these studies show that perceived social support (Han & Rojewski, 2015;Karacan-Özdemir & Yerin-Güneri, 2017), career indecision, and perceptions about gender roles (Yiğit, 2018) significantly predict career adaptability. In addition, career adaptability has a significant positive relationship with self-esteem (Ataç, Dirik, & Trigger, 2018;Hui, Yuen, & Chen, 2018) and different results are reported when examined by gender (Coetzee & Harry, 2015;Han & Rojewski, 2015;Erus & Zeren, 2017;Eryılmaz & Kara, 2018;Kahya & Ceylan, 2018). In studies that examine the relation between career adaptability and personality, personality is mostly examined in the context of the five-factor model of personality and these studies show that personality is significantly related to career adaptability (Norris, 2016;Eryılmaz & Kara, 2017).…”
Section: Introductionmentioning
confidence: 99%